The effects of environmental value and ecological worldview on eco-recreative attitude: An application in Turkey - Üzeyir KEMENT; Sinan ÇAVUSOGLU; Ismail ÇALIK; Yakup DURMAZ (Tourism & Management Studies)
This study aims to investigate the effect of environmental value and ecological worldview on eco-recreative attitude. In recent years human-related pollution has gravely increased and therefore it is important to explain the eco-recreative attitudes of participants with an emphasis on how eco-recreative supports natural life. Another indicator of the importance of this study is that it explains the premises of the attitude and that the eco-friendly attitude will become a life philosophy. The population of the study consists of individuals who participated in the ecoreaction event in Turkey. The data was collected through questionnaires using the convenience sampling method. The analyses were conducted through Smart PLS. Data analysis was made in two stages; measurement model and structural assessment. The study found that biospheric value has a positive effect on ecological worldview while ecological worldview has a positive effect on affective, cognitive and behavioral attitude.